No limits eaudiobook Ultimate series, book 1. - Foster, Lori (Ultimate, 2014)
A surprise inheritance reunites a mixed martial arts fighter with the woman he's never forgotten in the first in a smoldering new series from New York Times bestselling author Lori Foster Cannon Colter is quintessential hero material: chiseled jawline, shredded body-the works. He's also the guy who rescued Yvette Sweeny from kidnappers, only to put an end to her romantic dreams. These days, she's older, smarter, determined to face whatever life throws her way. Even the prospect of sharing a house and business with Cannon. Cannon knew Yvette wanted him three years ago. But she was young-and some things are worth waiting for. Thrown together by her grandfather's legacy, he realizes how deep Yvette's scars really go, and how much danger lurks in their quiet town. As pent-up desire explodes between them, protecting her becomes the only fight that matters. And he'll break all the rules to do it..